Poverty in the Pre-transition Period - experience of the selected eastern european countries - Велинка Томић (Acta Economica, 2021)
Process of transition in Eastern European countries is complex phenomena consisting of four parallel process: simultaneous process of economical, political, constructional and cultural transformation. Or, other way out its is process of creating market economy, political democracy, constitutional state and civil society. That is why transition causes a series of disturbances with, like poverty does, signifcant and heavy consequences for citizens. Word “poverty” means different for different people. It is very unique for specifc area, specifc groups, households or specifc persons, but there is no part of the world insensitive to poverty. Poverty is the multidimensional problem, and it must be treated multidimensional as some aspects are mutually related and caused (taken measures in one aspect can in?uence others). Experiences of the most successful transitional economies which are already members of the EU show that even starting conditions are of critical importance, but that crucial and reforms on the unifed levels are also important for growth. The analysis of the initial conditions which marked some economies and societies, might be helpful for better consideration of the transition process through the prism of poverty.